A method for real‐time temporal disaggregation of blended radar–rain gauge precipitation fields. (3rd November 2019) - Barton, Yannick; Sideris, Ioannis V.; Germann, Urs; Martius, Olivia
Abstract: A fully automated quasi‐real‐time method is presented to disaggregate hourly to sub‐hourly precipitation information operationally in a blended radar–rain gauge product. The method proposes a fully automated solution to disaggregate precipitation in regions characterized by measurement errors or partial absence of auxiliary information on the temporal precipitation evolution. The solution relies on a combination of low‐pass filtered radar information and stochastically generated noise fields. A comprehensive validation of the new method is provided demonstrating higher skill compared to a uniform disaggregation in time. The method is now an integral part of CombiPrecip, the official operational code of MeteoSwiss for radar–rain gauge merging. Abstract : A fully automated quasi‐real‐time method is presented to disaggregate hourly to sub‐hourly precipitation operationally in a blended radar–rain gauge product. The method proposes a fully automated and artefact‐free solution to disaggregate precipitation in regions characterized by measurement errors or partial absence of auxiliary information on the temporal precipitation evolution. The solution relies on a combination of low‐pass filtered radar information and stochastically generated noise fields.